2011
DOI: 10.1155/2011/473983
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Residual Body in the Spatial Organization of Toxoplasma gondii Tachyzoites within the Parasitophorous Vacuole

Abstract: Toxoplasma gondii proliferates and organizes within a parasitophorous vacuole in rosettes around a residual body and is surrounded by a membranous nanotubular network whose function remains unclear. Here, we characterized structure and function of the residual body in intracellular tachyzoites of the RH strain. Our data showed the residual body as a body limited by a membrane formed during proliferation of tachyzoites probably through the secretion of components and a pinching event of the membrane at the post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
(53 reference statements)
2
40
0
Order By: Relevance
“…Based on electron microscopy evidence, the RB has been predicted to be involved in the transfer of material between parasites within a vacuole (Muñiz-Hernández et al, 2011) although this has not been previously demonstrated. To investigate this hypothesis and the role of actin in this process, we infected host cells with wt or act1 cKO parasites expressing GFP and bleached individual parasites within the PV before measuring the time of fluorescence recovery (Videos 1 and 2; Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on electron microscopy evidence, the RB has been predicted to be involved in the transfer of material between parasites within a vacuole (Muñiz-Hernández et al, 2011) although this has not been previously demonstrated. To investigate this hypothesis and the role of actin in this process, we infected host cells with wt or act1 cKO parasites expressing GFP and bleached individual parasites within the PV before measuring the time of fluorescence recovery (Videos 1 and 2; Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Replication occurs via a unique process of endodyogeny, where two daughter parasites are constructed within the mother, before elongating and budding, leading to the breakdown of the maternal parasite (Francia and Striepen, 2014). Remnants of the mother cell remain at the posterior end of the daughter parasites in a structure known as the residual body (RB), which has a role in organizing the parasites into their characteristic rosette pattern within the PV (Muñiz-Hernández et al, 2011; Hu et al, 2002). Membrane connections persist between the RB and the parasites until host cell lysis and parasite egress, presumably to allow inter-parasite communication (Muñiz-Hernández et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, basal pole constriction indirectly participates in the formation or maintenance of the tubes connecting parasites following division. This connection between parasites is in continuity with the parasites plasma membrane and composes the RB [63]. More work is needed to define if MyoI is implicated in the formation of the connection and/or also in the active transport of material between parasites along the actin filaments visualized at the same location by using actin chromobodies [64 ].…”
Section: T Gondii Myosin I Promotes Cell-cell Communication Between mentioning
confidence: 99%
“…2). The fact that FIKK-YFP remained associated with the basal end of the parasite in extracellular parasites confirmed its localization within the parasite rather than the network between the tachyzoite posterior end and the residual body membrane within the parasite rosette (Muniz-Hernandez et al, 2011). …”
Section: Resultsmentioning
confidence: 90%